2013
DOI: 10.2478/prolas-2013-0005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of HHV-6 And HHV-7 in Patients After Kidney Transplantation

Abstract: Human herpesviruses HHV-6 and HHV-7 reactivation in transplantation is associated with indirect immunomodulatory effects, such as cytomegalovirus (CMV) disease, increased opportunistic infections, graft dysfunction and acute rejection (AR). In this study, we analysed the clinical and immunological outcomes in renal transplant recipients (RTR) with active HHV-6 and HHV-7 infection. Between January 2007 and December 2007, clinical, virological and immunological tests were carried out in 46 RTR. The patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The sero-prevalence rates of CMV and HHV-7 in RTR were (97.7%) and (32%) respectively. | P a g e Finally Table (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) involves correlations among the anti-CMV and HHV-7 IgG antibodies titers and viral loads of the three beta herpes viruses. Human CMV viral load (VL) is significantly increasing, and is significantl y correlated with the VL of both roseolaviruses after three months of follow up.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sero-prevalence rates of CMV and HHV-7 in RTR were (97.7%) and (32%) respectively. | P a g e Finally Table (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) involves correlations among the anti-CMV and HHV-7 IgG antibodies titers and viral loads of the three beta herpes viruses. Human CMV viral load (VL) is significantly increasing, and is significantl y correlated with the VL of both roseolaviruses after three months of follow up.…”
Section: Resultsmentioning
confidence: 99%
“…A growing body of evidence suggests that the major impact of HHV-6 and HHV-7 reactivation in transplantation is related to indirect immunomodulatory effects, such as their association with CMV disease, increased opportunistic infections, graft dysfunction and rejection (6,7) . Furthermore, other studies indicated that in kidney recipients with rejection, HHV-7 was more frequently associated with rejection episodes (32) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation